Mediators of mucosal integrity in the context of agriculture dust exposure - Chesterman, Carly Sue, author; Nordgren, Tara, advisor; Moreno, Julie, committee member; Podell, Brendan, committee member (Colorado State University. Libraries, 2023)
Inhalation of particulate matter, such as agricultural dust, can lead to lung inflammation and increased risk for chronic respiratory diseases. Agricultural workers, such as hog farmers, are constantly exposed to organic dusts from the workplace. Chronic pulmonary obstructive disease (COPD) is a type of lower respiratory disease, which results in an excessive inflammation cycle that leads to disease progression. Currently, available treatments merely treat the patient's symptoms with no effect on the prevention of disease progression. Metabolites of omega-3 fatty acids, called specialized pro-resolving mediators (SPM), can aid in inflammation resolution and promote immunity in the context of respiratory infection. IL-22 promotes mucosal immunity by regulating inflammation, inducing the production of antimicrobial peptides (AMP), and promoting epithelial repair. Mucosal surfaces in the airways are lined with epithelial cells, a mucus layer, and immune cells that act as the first line of defense against inhaled pathogens. The respiratory epithelium cells express antimicrobial peptides like beta-defensin-2 and Regenerating islet-derived protein 3 gamma (Reg3g); this expression can be stimulated by IL-22. In this study, we explored the effects of omega-3 fatty acids after organic dust exposure using a fat-1 transgenic mouse model, which represents the ideal ratio between omega-3 and omega-6 fatty acids. To further explore the impacts of IL-22 on AMP expression after organic dust exposure, a whole-body IL-22 knockout mouse model also was used in this study. Since omega-3 fatty acids and IL-22 promote inflammation resolution, we studied their impact on mucosal immunity and epithelial repair following repetitive challenges with extracts of organic dust in vivo. Wildtype, IL-22 knockout, and fat-1 mice were exposed by intranasal installations five times a week for 3 weeks. Lung tissue from mice exposed to either organic dust or saline were obtained and evaluated for AMP and wound repair markers. To evaluate the impact of IL-22 on AMP expression in the context of organic dust exposure, immunofluorescence (IF) staining, enzyme-linked immunosorbent assays (ELISAs), and RT-qPCR arrays were used. IF staining was done to assess beta-defensin-2 expression within the bronchial epithelial cells in IL-22 knockout and wildtype mice. While trends of positive staining for beta-defensin-2 were observed, no statistical significance was found. ELISAs were performed to assess for Reg3g expression in mice lung tissue; concentrations were found to be present in both the wildtype and IL-22 knockout models after saline and dust exposure. To assess for markers of wound repair in IL-22 knockout and wildtype mice models, a custom RT2 profiler PCR array was ordered to detect gene expression of different antimicrobial peptides, anti- and pro-inflammatory markers, and wound repair markers. The findings were as follows. Expression of AMPs—specifically S100A8 and S100A9—indicates a decrease among organic dust-exposed groups. The expression of wound repair markers CCL7 and ITGA3 exhibited decreases in the context of organic dust exposure. Expression of the anti-inflammatory marker MIF also exhibited a decrease among dust-exposed groups. To evaluate the impact of omega-3 fatty acids on AMP expression in the context of organic dust exposure, lung tissue from fat-1 and wildtype mice were stained for Reg3g expression. While trends of positive staining for Reg3g were observed, no statistical significance was found. IL-22 signaling exhibited trends of increased expression of AMP and pro-resolution mediators of mucosal integrity in the context of chronic dust exposure. Further studies should be conducted to determine the effects of omega-3 fatty acids on AMP expression in the context of organic dust exposure. These findings can be utilized to develop new treatment strategies for lung disease that focus on pro-resolution rather than solely anti-inflammatory methods.
Keywords: antimicrobial peptides; chronic pulmonary obstructive disease (COPD); specialized pro-resolving mediators; beta-defensin-2; agricultural dust exposure; reg3g